GENDER ISSUES IN MARY NORTON’S NOVEL ENTITLED “THE BORROWERS” : A LITERATURE REVIEW - Luh Riskayani; Ni Komang Arie Suwastini; Luh Gede Eka Wahyuni (SPHOTA: Jurnal Linguistik dan Sastra, 2021)
Feminist literary criticism has been focused on the marginalization of women in literary texts and the efforts to deconstruct patriarchy through counter texts, such as Mary Norton’s The Borrowers. This paper aims to review previous studies and expert opinions on Norton’s The Borrowers, especially the arguments in the form of feminist literary criticism. This study employed George’s (2008) model of literature review to review articles employing feminist literary criticism in "The Borrowers." The articles were gathered from books, academic journals, and previous studies on Norton’s The Borrowers. The review reveals that the novel depicted a feminine and masculine environment, constructing biased gender roles and labor division that triggered efforts to gain emancipation and independence in the female character. Telling about miniature family who survived by “borrowing” items from a human, The Borrower is centered towards the young female who deconstructed the traditional binary oppositions concerning the work division and spatial division between males and females. Besides, The Borrowers also presented women’s marginalization, women’s struggles, and gender identity. Such revelation might be useful to extend the fight for gender equity, especially for the children as the target readers. Abstrak Kritik sastra feminis telah difokuskan pada marginalisasi perempuan dalam teks sastra dan upaya untuk mendekonstruksi patriarki melalui teks tandingan, seperti The Borrowers karya Mary Norton. Tulisan ini bertujuan untuk mengkaji kajian-kajian terdahulu dan pendapat para ahli tentang The Borrowers karya Norton, khususnya argumentasi-argumentasi berupa kritik sastra feminis. Penelitian ini menggunakan model literature review George (2008) untuk mengkaji artikel-artikel yang menggunakan kritik sastra feminis dalam "The Borrowers". Artikel dikumpulkan dari buku, jurnal akademik, dan studi sebelumnya tentang The Borrowers dari Norton. Tinjauan terdahulu mengungkapkan bahwa The Borrowers menggambarkan lingkungan feminin dan maskulin, membangun peran gender yang bias dan pembagian kerja yang memicu gerakan emansipasi dan kemandirian dalam karakter wanita. Menceritakan tentang keluarga mini yang bertahan hidup lewat “meminjam” barang dari manusia, The Borrower berpusat pada perempuan muda yang mendekonstruksi oposisi biner tradisional mengenai pembagian kerja dan pembagian ruang antara laki-laki dan perempuan. Selain itu, The Borrowers juga menampilkan marginalisasi perempuan, perjuangan perempuan, dan identitas gender. Penceritaan tersebut dapat berguna untuk perpanjangan perjuangan kesetaraan gender terutama bagi anak-anak sebagai target pembaca.